Pengaruh Brand Awareness, Brand Image, dan Kualitas Produk Kopi Tuku GBK terhadap Loyalitas Konsumen dengan Kepuasan Konsumen sebagai Variabel Moderator: - - Ananda Syifa Yustian Putri; Muthia Arnetti Zahra; Akhmad Edhy Aruman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study examines the influence of brand awareness, brand image, and product quality of Kopi Tuku at the Gelora Bung Karno (GBK) branch on consumer loyalty, with consumer satisfaction serving as a moderating variable. As one of the pioneers of palm sugar coffee in Indonesia, Kopi Tuku has successfully established a reputation as a local coffee brand known for consistency in taste and service, yet it continues to face intense competition within the modern coffee industry. The research adopts a quantitative explanatory approach with purposive sampling involving 200 respondents who are customers of Kopi Tuku GBK. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings reveal that brand awareness does not have a significant effect on either consumer satisfaction or consumer loyalty. In contrast, brand image and product quality show a positive and significant influence, both directly and indirectly through consumer satisfaction, on loyalty. These results highlight the role of consumer satisfaction as a mediating variable that strengthens the relationship between brand image and product quality with loyalty. This study is expected to provide theoretical contributions to the literature on marketing communication based on the Stimulus–Organism–Response (S-O-R) framework, as well as practical insights for local coffee brands in designing branding strategies and maintaining consistent consumer experiences to foster long-term loyalty.